ANALISIS KINERJA KEUANGAN PERUSAHAAN OPERATOR TELEKOMUNIKASI YANG TERDAFTAR DI BURSA EFEK INDONESIA (SEBELUM PANDEMI, SAAT PANDEMI, DAN SETELAH PANDEMI COVID-19) - Daviq Dwi Rizkhi; Ana Sopanah Supriyadi; Muchlis Mas’ud (Bajang Institute, 2024)
The purpose of this study is to find empirical evidence of the condition of financial performance as measured by the financial ratio of telecommunications operator companies on the Indonesia Stock Exchange, before the pandemic, during the pandemic, and after the Covid-19 pandemic.The type of research is quantitative exploration by utilizing the financial ratio formula: Current Ratio, Net Profit Margin, Total Assets Turnover, and Debt to Assets Ratio of six telecommunications operator companies on the IDX, namely: Telkomsel, Indosat, Sarana Menara Nusantara, XL Axiata, Smatfren, and First Media. This study will prove the condition of financial performance as measured by the financial ratio, before the pandemic, during the pandemic, and after the Covid 19 pandemic. Nichael. The results of the study show that the average CR (Current Ratio) and TAT (Total Assets Turnover) of telecommunications operator companies on the IDX are relatively low, while NPM (Net Profit Margin) is relatively moderate, as is DAR (Debt to Assets Ratio) which is relatively good or ideal. Telkomsel is a cellular operator company with the best financial performance, followed by Indosat, then the other four operator companies. The effects of the Covid-19 pandemic did not affect the telecommunications operator companies, because these companies actually got a windfall during the pandemic, didn't people communicate more online during the pandemic, so Covid-19 did not affect these companies